EKSPLORASI CENDAWAN ENDOFIT DARI TANAMAN PADI SEBAGAI AGENS PEMACU PERTUMBUHAN TANAMAN (The Exploration of Endophytic Fungi from Oryza sativa as Plant Growth Promoting Agents) - Weni Wilia; Islah Hayati; Dwi Ristyadi (Bioplantae, 2012)
Endophityc fungi have been successfully isolated from Oryza sativa atLaboratory of Plant Disease, Agriculture Faculty University of Jambi. Theaim of this research was to get endophityc fungi from Oryza sativa. Therewere three (3) candidates of endophityc fungi that have been successfullyisolated. Pathogenosity test which was done showed that all of fungi wereendophityc fungi. Those fungi were identified as endophityc fungi due to theseed of paddy could growth normally in pure culture of endophityc fungi. Thethree of isolated endophityc fungi were identified as Hifa steril 1, Hifa steril 2,and Fusarium sp.Keyword: endophityc fungi, Oryza sativa